139k views
4 votes
Question below in image

Question below in image-example-1

1 Answer

5 votes

Answer:

m=4 n=5

Explanation:

2n-1 = 9 because 1 is negative you add it to the 9 so the equation becomes 2n=10 then divide 10 by 2 and you get n=5

m+8 = 3m subtract the lone m (or 1m) from the left to the 3m which gives you 2m=8 then divide 8 by 2 and you get m=4

plug in the numbers to check.

2n-1=9= (2x5)-1=9 | 10-1=9 | 9=9

m+8=3m= 4+8=(3x4) | 12=12

User Darkstar Dream
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.